Evaluación y mejoramiento de prácticas agronómicas. Investigación a nivel de finca - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
During 1984-85, 98 trials were planted by CIAT- Instituto Colombiano Agropecuario (ICA) in 4 areas of Colombia (eastern Antioquia and southern, central, and northern Narino). These trials were of 5 types: var., exploratory, determination of economic levels, verification, and farmer-managed. The expansion of training in on-farm research and of participation in network activities was also important. As a direct result of recommendations derived by ICA- CIAT on-farm research, ICA released var. Frijolica 0-3.2 for cold climates and var. frijolica LS-3.3 for moderate cool climates. (CIAT)